Blood lactate levels during exercise : the effects of exercise duration, bicarbonate infusion and beta-receptor antagonism - Bertram, Sheila Rae (MRC/UCT RU for Exercise and Sport Medicine, 2018)
This study examines factors that determine blood lactate accumulation during exercise in order to examine the opposing theories that such accumulation occurs either as a result of muscle anaerobiosis or an "overflow" of oxygen-independent glycolysis.